Studi Kelayakan Bisnis Show Room Sepeda Motor Bekas - Heri Wibowo (Universitas Malahayati, 2013)
Motorcycle showroom is a business that can generate high profits. With the development of various businesses in the district of Tulang Bawang Barat, the Tumijajar is one area where demand is high motorcycle. Plus the nature of a consumer soci ety in which they always want things quickly. The first stage in the evaluation of the feasibility of a motorcycle showroom business is by way of collecting data is data the total population, the n umber of motorcycles and operating revenues followed by the business feasibility of processing methods Payback Period, Net Persent Value and Internal Rate of Return and further by analyzing st rengths, weaknesses, opportunities and threats through a SWOT analysis. The results showed that an investment of Rp 250.000.000 which is running on a motorcycle showroom victorious run properly pr imed with payback period of 1 year 4 months Persent Net Value of Rp 565.491.999, and the value of Internal Rate of Return of 83% and the concept of the marketing mix of the company has several fac tors that affect the strength, weaknesses, opportunities and threats. Where the company's posi tion in the Progressive position or positions that signifies a strong organization and opportunity. In other words, the organization in good shape and steady so it is possible to continue to expand, inc rease growth and achieve maximum progress. The Company has the right concept marketing mix but sti ll need to fix some weaknesses of the company and to avoid or defend against the threat of the co mpany by developing the concept of the existing mix. Keywords: Payback Period, NPV, IRR, SWOT analysis